Making Sense of the Aggregate Demand-Supply Model - Amit Bhaduri; Kazimierz Laski; M. Riese (The Vienna Institute for International Economic Studies (wiiw), 1995)
This paper questions the validity of using the aggregate demand (AD) and aggregate supply (AS) framework for analysing macroeconomic issues. AD derived from the Keynesian income-expenditure approach cannot be reconciled logically with AS derived from the profit maximization postulate in out-of-equilibrium positions. The paper shows two routes to achieving consistency, either by taking recourse to Kalecki's work or by entirely reformulating the analysis along neo-classical lines. Using these two polar cases, it reinterprets the model underlying Keynes' General Theory and modern disequilibrium analysis based on "rationing".
Keywords: 330; Aggregate demand (AD); aggregate supply (AS); incompatibility of AD/AS; consistent AD/AS reformulations; profit maximization and multiplier analysis; disequilibrium theory and short side of the market